Perbandingan Metode Pieces Dan System Usability Scale Untuk Menganalisa Kepuasan Pengguna Pada Sistem Penyewaan Mobil Berbasis Android - Rima Tamara Aldisa; Erwin Samudra; Rossa Sahara (JURIKOM (Jurnal Riset Komputer), 2022)
The research aims to build a car rental information system aimed at consumers who want to rent a car. With this system, car rental is more efficient and makes it easier to find out how satisfied and comfortable consumers are. This system is made using the Pieces method, with measurements of 6 aspects or variables, namely from the aspects of Performance, Information, Economics, Control, Effeciency, Service. The results of the Pieces analysis show the measurement of the level of user satisfaction. The System Usability Scale method or abbreviated as SUS here is an estimate to facilitate measurement and SUS has several appropriate questions. This system aims for consumers who are looking for an android-based car rental to analyze user satisfaction with the discount method which produces a value of 3,845 which is average and satisfactory, with a comparison of the SUS method getting an average value of 72 it can be said to be the same as the discount method, which is satisfactory. So it can be said that the users of the system here, namely consumers of car rentals, are satisfied with the system that has been designed based on Android